Babesia bovis expresses a neutralization-sensitive antigen that contains a microneme adhesive repeat (MAR) domain - Silva, Marta G. (2010)
A gene coding for a protein with sequence similarity to the Toxoplasma gondii micronemal 1 (MIC1) protein that contains a copy of a domain described as a sialic acid-binding micronemal adhesive repeat (MAR) was identified in the Babesia bovis genome. The single copy gene, located in chromosome 3, contains an open reading frame encoding a putative 181 amino acid protein, which is highly conserved among distinct B. bovis strains. Antibodies against both recombinant protein and synthetic peptides mimicking putative antigenic regions in the B. bovis-MIC1 (Bbo-MIC1) protein bind to the parasite in immunofluorescence assays and significantly inhibit erythrocyte invasion in in vitro B. bovis cultures. Bbo-MIC1 is recognized by antibodies in serum from B. bovis infected cattle, demonstrating expression and immunogenicity during infection. Overall, the results suggest that Bbo-MIC1 protein is a viable candidate for development of subunit vaccines. © 2010 Elsevier Ireland Ltd.